Kliwonan dalam Perspektif Historis dan Sosial Budaya Masyarakat Batang - Ambar Hermawan (LPPM UIN K.H. Abdurrahman Wahid Pekalongan, 2017)
Kliwonan Tradition is a cultural ritual for Batang society which is held every Friday every Kliwon selapanan (35 days) located in the square and the Great Mosque Batang. The event was conducted as an expression of gratitude and commemorate the services of the ancestors in the opening of Batang land and fight for Islam in the Batang region. This study aims to determine the history, value and meaning of Kliwonan in socio-cultural perspectives of Batang society. This study uses a qualitative approach, with data collected through observation methods, interviews, documents and questionnaires as supporting data. Data analysis using qualitative descriptive analysis technique. The results showed the response of Batang society to the tradition of Kliwonan ritual is quite strong. The majority of the community showed a strongly agreed attitude to the Kliwonan event which is the hallmark of Batang district. The results of interviews with various people who respond differently. The clerics responded that Kliwonan was merely a tradition, the myths circulating in society were in fact created. Cultural circles actually think Kliwonan has metamorphas from the mystical ritual transformed into a show that is only economically charged.